Experimental and Numerical Analysis of Epoxy Based Adhesive Failure on Mono- and Bi-Material Single Lap Joints Under Different Displacement Rates (Fracture and Structural Integrity, 2020)
Development in material science impose to use different materials in production. This causes a problem for joining different materials because traditional joining techniques such as welding could not overcome this problem in industries such as automotive. Hence, adhesive bonding overcomes this problem by its superiorities to join different materials. Joint strength of epoxy-based adhesives are affected by adhesive thickness, adherent’s surface quality and curing conditions. In this study, two different materials (SAE 304 and AL7075) were bonded by epoxy adhesive (3M DP460NS) as single lap joint (SLJ) of Aluminum-Aluminum, Steel-Steel and Aluminum-Steel. Effects of adhesive thickness (0.05, 0.13, 0.25 mm) and surface roughness (281, 193, 81 nm) to strength were compared. SLJs were tested for 1, 10, 25 and 50 mm/min displacement rates. Adhesive surface structures were imaged by Scanning Electron Microscopy (SEM) to investigate adhesive fractures. Surface roughness’s were examined by using Atomic Force Microscopy (AFM) to compare its influence on failure load. Finite Element Analysis (FEA) were conducted by using Cohesive Zone Model with ANSYS 18.0 software to obtain stress distribution of adhesive.Optimum values according to the present conditions of thickness(0.13mm) and roughness(
Keywords: Single lap joint; Epoxy adhesive; Displacement rate; Thickness; Surface roughness